Analytic and numerical solutions for axisymmetric flow with partial slip. (January 2016) - Ali, Ramzan; Shahzad, Azeem; Khan, Masood; Ayub, Muhammad
Abstract This article deals with the slip effects on the axisymmetric flow of an electrically conducting viscous fluid in the presence of a magnetic field over a non-linear radially stretching sheet. By introducing new similarity transformations, the governing partial differential equations are reduced to an ordinary differential equation. The resulting ordinary differential equation is then solved analytically using the homotopy analysis method and numerically by shooting method to show the accuracy of the analytical solution. The significant effects of various parameters on velocity field are discussed in detail. The shear stress at the wall together with some other physical parameters is tabulated and compared with existing literature, which shows an excellent agreement.